Menumbuhkan (Kembali) Kearifan Lokal dalam Pengelolaan Sumberdaya Alam di Tapanuli Selatan - Zulkifli Lubis (Antropologi Indonesia, 2005)
Studies on local knowledge are recently important in development program. Such studies remind us to learn from the community before we teach them. This article discusses how local knowledge understood and used to encourage people participation in forest conversation in South Tapanuli, North Sumatera. The author argues that local knowledge in forest management can be revitalized to build participation if only all stakeholders able to make social commitment as part of social capital. Key words: local knowledge; territoriality; tenure; natural resources.